Pengaruh Pengaruh Pendapatan Asli Daerah, Pendidikan dan Pengangguran Terhadap Kemiskinan di Provinsi Bali - Darmawan, Agus Pande; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
Poverty is a condition of life for underprivileged are in a natural person or household that can not meet the minimum requirements or eligible for life This study aims to determine the effect simultaneously and partially PAD, education, unemployment and poverty in the province of Bali. The data used in this research is secondary data. Data collection method used in this research is the case study method. The analysis technique used in this research is multiple linear regression analysis, which is accompanied with the classical assumption. PAD results obtained test results, education, and unemployment simultaneously significant effect on poverty in the province of Bali. Partially PAD and significant negative effect of education on poverty in the province of Bali. Meanwhile, in partial unemployment positive and significant impact on poverty in the province of Bali.